Boiler tube failures in thermal power plant: Two case studies. (2022) - Kumar, Shivam; Tadge, Prashant; Mondal, Abhijit; Hussain, Nasir; Ray, Subrata; Saha, Atanu
Abstract: This article presents failure investigation of two different boiler tubes in thermal power plant made of T22 grade. Detailed investigation including visual inspection, hardness measurement, chemical composition and metallography were conducted on both the failed tubes. The results conclude that first tube was failed due to creep damage and another tube was failed due to combined effect of erosion and corrosion. Recommendations were discussed as well to mitigate similar failures in power industries in near future.